التمويل بالسلم في المصارف الإسلامية، ضوابطه ومخاطره وآثاره الاقتصادية: Salam Financing in Islamic Banks: Shariah Regulations, Risk Management, and Economic Implications - أحمد بن الحسن الشمراني (Journal of North African Economies, 2025)
This study aims to shed light on the Salam contract as one of the Islamic financing instruments applied in Islamic banks, as well as the risks associated with its implementation and the methods of managing and mitigating those risks. It also highlights the economic impacts resulting from Salam-based financing. The study concludes that the application of Salam financing in Islamic banks is feasible and can be implemented efficiently and effectively, with the potential to hedge against and minimize the associated risks. This, in turn, contributes to positive economic outcomes for both individuals and the economy at large. Keywords: Salam, Salam Sale, Salam financing, Islamic finance, Islamic economics.